Susceptibility‐based time‐resolved whole‐organ and regional tissue oximetry. (26th February 2016) - Wehrli, Felix W.; Fan, Audrey P.; Rodgers, Zachary B.; Englund, Erin K.; Langham, Michael C.
Abstract : The magnetism of hemoglobin – being paramagnetic in its deoxy and diamagnetic in its oxy state – offers unique opportunities to probe oxygen metabolism in blood and tissues. The magnetic susceptibility χ of blood scales linearly with blood oxygen saturation, which can be obtained by measuring the magnetic field ΔB of the intravascular MR signal relative to tissue. In contrast to χ, the induced field ΔB is non‐local. Therefore, to obtain the intravascular susceptibility Δχ relative to adjoining tissue from the measured ΔB demands solution of an inverse problem. Fortunately, for ellipsoidal structures, to which a straight, cylindrically shaped blood vessel segment conforms, the solution is trivial. The article reviews the principle of MR susceptometry‐based blood oximetry. It then discusses applications for quantification of whole‐brain oxygen extraction – typically on the basis of a measurement in the superior sagittal sinus – and, in conjunction with total cerebral blood flow, the cerebral metabolic rate of oxygen ( CMRO 2 ). By simultaneously measuring flow and venous oxygen saturation ( SvO 2 ) a temporal resolution of a few seconds can be achieved, allowing the study of the response to non‐steady‐state challenges such as volitional apnea. Extensions to regional measurements in smaller cerebral veins are also possible, as well as voxelwise quantification of venous blood saturation in cerebral veins accomplished by quantitative susceptibility mapping (QSM) techniques. Applications of susceptometry‐based oximetry to studies of metabolic and degenerative disorders of the brain are reviewed. Lastly, the technique is shown to be applicable to other organ systems such as the extremities using SvO 2 as a dynamic tracer to monitor the kinetics of the microvascular response to induced ischemia. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Quantification of reactive hyperemia with dynamic oximetry showing cross‐sectional phase difference image of the thigh, 10 cm below the inferior boundary of the pressure cuff along with post‐ischemia femoral vein SvO 2 time course, and series of zoomed phase images showing relative phase of venous blood during period indicated. Darker blue represents lower saturation levels. Parameterization of time‐course data yields quantitative metrics: washout time, upslope and overshoot.